Perencanaan Saluran Irigasi Sub Daerah Irigasi Onggok Atas Pada Daerah Irigasi Banjarcahyana, Kabupaten Banjarnegara, Jawa Tengah - Koten, Agustinus Doro Ruro; Kiki Frida , Sulistyani; Suhudi, Suhudi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Agricultural land always needs water to maintain its fertility. Water is a source of nutrients and nutrients that act as fertilizers for land and agricultural crops. At this time the land area of the Onggok Atas sub-irrigation area, Banjarcahyana Irrigation Area has not been able to obtain irrigation water evenly in the sense of sufficient quantity and the right time. This is due to, among other things, the condition of the irrigation network has decreased its capacity. This study aims to determine the need for irrigation water in rice fields, to determine the need for water in the channel and to determine the dimensions of the Onggok Atas secondary channel. Researchers conducted a review of secondary channels by collecting secondary data for the calculation of hydrological analysis, irrigation water needs using KP 01 and 03 guidebooks and later obtained the cross-sectional size of secondary irrigation channels. Based on the results of the analysis that has been calculated on an area of 316.10ha and the length of the secondary channel is 4881m, the irrigation water requirement in rice fields is 1.11lt/dt/ha for rice and 0.89lt/dt/ha for secondary crops. The water requirement upstream is 488.25lt/dt = 0.488m3/dt and the water requirement downstream is 100.67lt/dt = 0.101m3/dt. The dimensions of the largest irrigation secondary channel are B.OA 1, Stream Cross Section, (A) = 0.919m2 with width (b) = 0.95m and height (H) = 0.79m, and the dimensions of the smallest irrigation secondary channel are B.OA 6, Stream Cross Section, (A) = 0.171m2 with width (b) = 0.45m and height (H) = 0.45m.